(untitled) (Journal of Educational Sciences, 2023)
The article provides a study of the Republic of Kazakhstan’s "Social Pedagogue" professional standard in terms of the measurability and non-measurability of skills and abilities by meters that are currently utilized in the country as part of the National Qualification Tests (NQT). This is the sole qualification examination administered in the field of education. In the context of the NQT, specialists in the field of education (teachers working in schools; future teachers, i.e., graduates of pedagogical universities; social educators, etc.) are subjected to testing in which their subject-matter knowledge in particular fields is evaluated. The goal of this article is to determine if the format of the present qualifying exam is consistent with the expected results of the professional standard, which outlines the required knowledge, skills, and abilities of social educators. An review of these requirements revealed that the current instrument for assessing the readiness of social educators to engage in professional activities is insufficient for determining the specialists’ degree of preparedness. Within the context of our article, we present our solution to this issue. A focus group study was conducted, in which 190 future social educators studying at universities of the Republic of Kazakhstan took part. As a result of the study, three most common problems were identified: the inability to control children’s visits to social networks; the difficulty of working with migrant families; the increase in autistic children. A social pedagogue interacts with students, their parents, teachers, social workers, psychologists, juvenile inspectors, and many others in the course of his profession. Due to this, it is vital to pay close attention to the training of specialists and to change the instrument used to determine their professional level. Key words: qualifying exam, qualification, professional standard, assessment of the readiness of specialists, measurability and non-measurability of skills, assessment procedure.